2020
DOI: 10.1515/jpm-2020-0446
|View full text |Cite
|
Sign up to set email alerts
|

Initial review of pregnancy and neonatal outcomes of pregnant women with COVID-19 infection

Abstract: ObjectivesData regarding the pathogenesis and clinical manifestations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to emerge, however, there’s limited data in regard to maternal and neonatal outcomes. Therefore, we conducted a retrospective analysis of all pregnant women who tested positive for SARS-CoV-2 within Nuvance Health system.Study designData were abstracted from the medical records of each patient and descriptive analysis was performed. Variables included demographics, COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 10 publications
0
4
0
12
Order By: Relevance
“…Las condiciones asociadas al embarazo más frecuentes fueron la preeclampsia, descrita en 5 artículos (13,15,16,19,20), con frecuencias del 0,6 % ( 16) hasta el 23,3 % (19) de casos; no obstante, cuando la condición de la paciente fue crítica, se encontró hasta en un 40,4 % (19) de los casos. La hemorragia posparto fue descrita en 5 artículos (12,15,16,18,19), con frecuencias del 1,3 % ( 16) hasta el 25 % (18) de los casos. El aborto espontáneo se reportó en 5 artículos (12,13,19,21,22), con frecuencias del 1 % (19) hasta el 14,2 % (13) de los casos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Las condiciones asociadas al embarazo más frecuentes fueron la preeclampsia, descrita en 5 artículos (13,15,16,19,20), con frecuencias del 0,6 % ( 16) hasta el 23,3 % (19) de casos; no obstante, cuando la condición de la paciente fue crítica, se encontró hasta en un 40,4 % (19) de los casos. La hemorragia posparto fue descrita en 5 artículos (12,15,16,18,19), con frecuencias del 1,3 % ( 16) hasta el 25 % (18) de los casos. El aborto espontáneo se reportó en 5 artículos (12,13,19,21,22), con frecuencias del 1 % (19) hasta el 14,2 % (13) de los casos.…”
Section: Resultsunclassified
“…Se identificaron inicialmente 2618 artículos y se añadió luego el filtro de estudios observacionales, que resultó en 49 artículos. De estos se leyeron títulos y resúmenes y, finalmente, se incluyeron 15 artículos (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), que responden a la pregunta de investigación.…”
Section: Materiales Y Métodosunclassified
“…We included 34 primary studies that were not case reports. The primary studies included eight case series (Chaudhary S 2020, Liu W 2020, Masmejan S 2020, Olivini N 2020, Pereira A 2020, Pissarra S 2020, Zhang P 2020, 21 cohort studies (either prospective or retrospective) (Anand P 2020, Ayed A 2020 , Bachani S 2020, Barbero P 2020, Gale C 2020, Fenizia B 2020, He Z 2020, Hu X 2020, Luo Q 2020, Khan MA 2020, Nayak AH 2020, Ogamba I 2020, Oncel MY 2020, Maraschini A 2020, Popofsky S 2020, Smithgall MC 2020,Tang F 2020, Vinuela MC 2020, Vouga M 2020,Yang R 2020, 2 retrospective observational studies , Moreno SC 2020. and one quality improvement project (Cojocaru L 2020), one longitudinal surveillance study (Woodworth KR 2020), and one multi-centre retrospective chart review (Marin Gabriel MA 2020.…”
Section: Primary Studiesmentioning
confidence: 99%
“…The studies included symptomatic and asymptomatic women; however there did not seem to be a specific correlation between symptom status of the mothers and the likelihood of a positive test in the babies, with some studies reporting on women who had symptoms of COVID-19 either immediately prior to or during hospitalisation, some with severe symptoms, where none of the babies tested positive within 24h of birth (e.g. Liu W 2020, Luo Q 2020, Masmejan S 2020, Moreno SC 2020, Ogamba I 2020, Popofsky S 2020 (See Table 1a). Similarly, the mode of delivery (vaginal birth, caesarean section, emergency caesarean section) did not seem to be correlated to positivity rate amongst neonates; across the included cohort and case series studies, for the 6188 cases where mode of delivery was reported, 3939 were by vaginal delivery, 2122 by caesarean section, and 127 reported as emergency caesarean (Table 1b).…”
Section: Primary Studiesmentioning
confidence: 99%
See 1 more Smart Citation